2018
DOI: 10.1038/s41526-018-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia in austere environments: literature review and considerations for future space exploration missions

Abstract: Future space exploration missions will take humans far beyond low Earth orbit and require complete crew autonomy. The ability to provide anaesthesia will be important given the expected risk of severe medical events requiring surgery. Knowledge and experience of such procedures during space missions is currently extremely limited. Austere and isolated environments (such as polar bases or submarines) have been used extensively as test beds for spaceflight to probe hazards, train crews, develop clinical protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
6

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(83 citation statements)
references
References 108 publications
(241 reference statements)
0
77
0
6
Order By: Relevance
“…Silverman and McCartney support the use of regional anesthesia, but indications are mostly limited to limb injuries, training requirements are high and the failure rate ought not to be underestimated in practice. Specific sedation and GA protocols have been suggested for spaceflight . A pilot study suggested that unassisted personnel with minimal medical training may be able to perform a GA with intubation during a Mars mission …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Silverman and McCartney support the use of regional anesthesia, but indications are mostly limited to limb injuries, training requirements are high and the failure rate ought not to be underestimated in practice. Specific sedation and GA protocols have been suggested for spaceflight . A pilot study suggested that unassisted personnel with minimal medical training may be able to perform a GA with intubation during a Mars mission …”
Section: Discussionmentioning
confidence: 99%
“…ISS testing of these concepts would be desirable, but challenging to achieve in light of transportation costs to low Earth orbit. Furthermore, the medical problems during ISS presence as well as on the Mars are of utmost importance and require future research activities . Both the laws of physics and its impact on how to perform anesthesia and surgery must be theoretically planned and tested practically to build up a feasible and safe concept for long‐duration space missions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations